Systematic evaluation of biophysical and functional characteristics of selenomethylene-locked nucleic acid-mediated inhibition of miR-21 - Nahar, Smita; Singh, Amrita; Morihiro, Kunihiko; Moai, Yoshihiro; Kodama, Tetsuya; Obika, Satoshi; Maiti, Souvik (Biochemistry, 2016)
miRNAs constitute an important layer of gene regulation mediated by sequence-specific targeting of mRNAs. Aberrant expression of miRNAs contributes to a host of pathological states. Promoting cancer, miR-21 is upregulated in variety of cancers and promotes tumor progresion by suppressing a network of tumor suppressor genes. Here we describe a novel class of bicyclic RNA analogues, selenomethylene-locked nucleic acid (SeLNA), that display high affinity, improved metabolic stability, and increased potency for miR-21 inhibition. The thermal stability (T-m) for duplexes was increased significantly with incorporation of SeLNA monomers as compared to that of the unmodified DNA RNA hybrid. A comprehensive thermodynamic profile obtained by isothermal titration calorimetry revealed a favorable increase in the enthalpy of hybridization for SeLNA containing DNA and target RNA heteroduplexes. SeLNA modifications displayed remarkable binding affinity for miR-21 target RNA with a K-a of <= 1.05 x 10(8) M-1. We also observed enhanced serum stability for SeLNA RNA duplexes with a half-life of <= 36 h. These in vitro results were well correlated with the antisense activity in cancer cells imparting up to similar to 91% inhibition of miR-21. The functional impact of SeLNA modifications on miR-21 inhibition was further gauged by investigating the migration and invasion characterisitics of cancer cells, which were drastically reduced to similar to 49 and similar to 55%, respectively, with SeLNA having four such modifications. Our findings demonstrate SeLNA as a promising candidate for therapeutics for disease associated miRNAs.

G-quadruplex motif at the 3' end of sgRNAs improves CRISPR-Cas9 based genome editing efficiency - Nahar, Smita; Sehgal, Paras; Azhar, Mohammad; Rai, Manish; Singh, Amrita; Sivasubbu, Sridhar; Chakraborty, Debojyoti; Maiti, Souvik (Chemical Communications, 2018)
Originating as a component of prokaryotic adaptive immunity, the type II CRISPR/Cas9 system has been repurposed for targeted genome editing in various organisms. Although Cas9 can bind and cleave DNA efficiently under in vitro conditions, its activity inside a cell can vary dramatically between targets owing to differences between genomic loci and availability of enough Cas9/sgRNA (single guide RNA) complex molecules for cleavage. Most methods to improve CRISPR/Cas9 activity have so far relied on Cas9 protein engineering or base modifications in the sgRNA sequence. Here we demonstrate that a structure based rational design of sgRNAs can enhance the efficiency of Cas9 cleavage in vivo. By appending a naturally forming RNA G-quadruplex motif to the 3′ end of sgRNAs we can improve its stability and target cleavage efficiency in zebrafish embryos without inducing off-target activity, thereby underscoring its value in the design of better and optimized genome editing triggers.

Visible-light-active unsymmetrical squaraine dyes with 1 V of open-circuit voltage for dye-sensitized solar cells - Singh, Amrita; Kumar Singh, Ambarish; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ChemPhotoChem, 2023)
A series of alkyl-group-functionalized, aniline- and indoline-donor-based, unsymmetrical visible-light-active squaraine dyes, AM1-3, were designed and synthesized. Dye-sensitized solar cell (DSSC) devices were fabricated with both I-/I-3(-) and [Cu(tmby)(2)](+/2+) electrolytes. DSSC devices sensitized with the AM1 and AM2 dyes showed relatively high-power conversion efficiency of 7.44 % and 7.22 %, respectively with I-/I-3(-) in the absence of chenodeoxycholic acid (CDCA) than those of the AM3 dye (5.41 %). The [Cu(tmby)(2)](+/2+) electrolyte along with poly(3,4-ethylenedioxythiophene) (PEDOT) as cathode material showed excellent open-circuit potentials (V-OC) of 1030, 1025, and 1001 mV with the DSSC efficiency of 8.05 %, 7.96 %, and 5.84 %, respectively, for the AM1, AM2, and AM3 dyes in the absence of CDCA. Here, the AM1 dye exhibited the maximum DSSC efficiency of 8.05 % and V-OC of 1030 mV, which is the highest obtained efficiency and V-OC for the visible-light active zwitterionic unsymmetrical-squaraine dye with copper-based electrolyte.
Keywords: Cu electrolytes; dihedral angle; Dye-sensitized solar cells; open circuit voltage; squaraine dyes

Effect of position of donor units and alkyl groups on dye-sensitized solar cell device performance: indoline-aniline donor-based visible light active unsymmetrical squaraine dyes - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Om., 2024)
Indoline (In) and aniline (An) donor-based visible light active unsymmetrical squaraine (SQ) dyes were synthesized for dye-sensitized solar cells (DSSCs), where the position of An and In units was changed with respect to the anchoring group (carboxylic acid) to have In-SQ-An-CO2H and An-SQ-In-CO2H sensitizers, AS1-AS5. Linear or branched alkyl groups were functionalized with the N atom of either In or An units to control the aggregation of the dyes on TiO2. AS1-AS5 exhibit an isomeric pi-framework where the squaric acid unit is placed in the middle, where AS2 and AS5 dyes possess the anchoring group connected with the An donor, and AS1, AS3, and AS4 dyes having the anchoring group connected with the In donor. Hence, the conjugation between the middle squaric acid acceptor unit and the anchoring -CO2H group is short for AS2, AS5, and AK2 and longer for AS1, AS3, and AS4 dyes. AS dyes showed absorption between 501 and 535 nm with extinction coefficients of 1.46-1.61 x 10(5) M-1 cm(-1). Further, the isomeric pi-framework of An-SQ-In-CO2H and In-SQ-An-CO2H exhibited by means of changing the position of In and An units a bathochromic shift in the absorption properties of AS2 and AS5 compared to the AS1, AS3, and AS4 dyes. The DSSC device fabricated with the dyes contains short acceptor-anchoring group distance (AS2 and AS5) showed high photovoltaic performances compared to the dyes having longer distance (AS1, AS3, and AS4) with the iodolyte (I-/I-3(-)) electrolyte. DSSC device efficiencies of 5.49, 6.34, 6.16, and 5.57% have been achieved for AS1, AS2, AS3, and AS4 dyes, respectively; without chenodeoxycholic acid (CDCA), small changes have been observed in the device performance of the AS dyes with CDCA. Significant changes have been noted in the DSSC parameters (open-circuit voltage V-OC, short-circuit current J(SC), fill factor ff, and efficiency eta) for the AS5 dye while sensitized with CDCA and showed highest DSSC efficiency of 8.01% in the AS dye series. This study revealed the potential of shorter SQ acceptor-anchoring group distance over the longer one and the importance of alkyl groups on the overall DSSC device performance for the unsymmetrical squaraine dyes.

Visible, far-red, and near-infrared active unsymmetrical squaraine dyes based on extended conjugation within the polymethine framework for dye-sensitized solar cells - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Alkyl group wrapped visible, far-red, and NIR active unsymmetrical squaraine dyes with pi-extension in the polymethine framework-based AM4-AM7 have been designed, synthesized, and utilized as sensitizers for dye-sensitized solar cells. To extend the pi-conjugation within the polymethine framework, thiophene moieties have been incorporated between the donor and acceptor moieties. Absorption spectroscopic studies revealed that pi-extension with each -C & boxH;C- unit resulted similar to 100 nm of redshift in the charge transfer transition with the lambda(maximum) of 541, 643, 747, and 833 nm for AM4, AM5, AM6, and AM7 dyes, respectively, with the molar extinction coefficient of >10(5) M(-1)cm(-1). The pi-extended conjugation-based AM6 and AM7 dyes showed improved light-harvesting efficiency (LHE), where the AM7 dye showed an LHE of 386 nm at 60%. Electrochemical studies of AM dyes revealed that the HOMO energy level of the sensitizers has been modulated systematically. Further, pi-extension within the polymethine framework showed a dramatic effect on V-OC, J(SC), and device efficiency when move from visible active AM4 to far-red active to NIR active AM7 dyes. The DSSC efficiencies of 7.35, 5.18, 0.08, and 0.053% have been achieved with the I-/I-3(-) electrolyte (Z-50) for the AM4, AM5, AM6, and AM7 dyes, respectively. Further, AM4 dye has been cosensitized with AM5, AM6, and AM7 dyes, where AM4:AM5 (1:1) composition achieved the maximum efficiency of 8.12% with I-/I-3(-) electrolyte (Z-50) compared to the other cosensitization compositions.
Keywords: aggregation of dyes; DSSC device efficiency; light-harvesting efficiency; pi-extension; polymethine framework; squaraine dyes